Epstein-Barr Virus Encephalitis: A Case Report - HASHEMIAN, Somayh; ASHRAFZADEH*, Farah; AKHONDIAN, Javad; BEIRAGHI TOOSI, Mehran (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Hashemian S, Ashrafzadeh F, Akhondian J, Beiraghi Toosi M. Epstein-Barr Virus Encephalitis: A Case Report. Iran J Child Neurol. 2015 Winter;9(1):107-110. Abstract Many neurologic manifestations of Epstein-Barr virus (EBV) infection have been documented, including encephalitis, aseptic meningitis, transverse myelitis, and Guillain-Barre syndrome. These manifestations can occur alone or coincidentally with the clinical picture of infectious mononucleosis. EBV encephalitis is rare and is indicated as a wide range of clinical manifestations. We report a 10-year-old girl presented with fever, gait disturbance, and bizarre behavior for one week. The results of the physical examination were unremarkable. The diagnosis of EBV encephalitis was made by changes in titers of EBV specific antibodies and MRI findings. A cranial MRI demonstrated abnormal high signal intensities in the basal ganglia and the striatal body, especially in the putamen and caudate nucleus. EBV infection should be considered when lesions are localized to the basal ganglia. References Fujimoto H, Asaoka K, Imiazumi T, Ayabe M, Shoji H, Kaji M. Epstein-Barr virus Infections of the Central Nervous System. Intern Med 2003; 42:33-40. Mathew AG, Parvez Y. Fulminant Epstein Barr virus encephalitis. Indian Pediatrics 2013; 50:418-419 Kalita J, Maurya PK, Kumar B, Misra UK. Epstein Barr virus encephalitis: Clinical diversity and radiological similarity. Neurol India 2011; 59:605-7 Baskin HJ, Hedlund G. Neuroimaging of Herpes Virus Infections in Children. Pediatr Radiol 2007; 37:949-63. Weinberg A, Li SH, Palmer M, Tyler K .Quantitative CSF PCR in Epstein-Barr Virus Infections of the Central Nervous System. Ann Neurol 2002; 52:543-8. Ono J, Shimizu K, Harada k, Mano T, Okada S. Characteristic MR Features of Encephalitis Caused by Epstein-Barr virus. Pediatr Radiol 1998; 28:569-70. Hausler M, Raamaekers T, Doenges M, Shweizer K ,Ritter K. Neurological Complications of Acute and Persistent Epstein-Barr Virus Infection in Pediatric Patients. Journal of Medical Virology 2002; 68:253-63. Young JY, Hyang LK. Transient Asymptomatic White Matter Lesions Following Epstein-Barr virus Encephalitis. Korean pediatric society 2011; 54:389- 93. Doja A, Bitnun A, Jones EL, Richardson S, Tellier R, Petric M, et al. Pediatric Epstein-Barr Virus-Associated Encephalitis:10-Year Review. Child Neurol 2006; 21:385-91. Kou K, Itoh M, Kawano Y. A Case Report of EB Virus- Induced Meningoencephalitis Associated with Brain MRI Abnormalities (basal ganglia). J Japan Peditr Sos 1994; 98:2052-9. Kunlong H, Hung-Tsai L, Minlan T. Epstein-Barr Virus Encephalitis in Children. Acta Pediatrica Taiwanica 2000; 3:140-6.